PERANANAN PANTI ASUHAN DALAM MENUNJANG PENDIDIKAN ANAK ASUH (STUDI KASUS LKSA PANTI ASUHAN MUHAMMADDIYAH CINGKARIANG) - Nani Febi Nur Aini; Afrinaldi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article aims to explore the activities and parenting styles implemented at the Muhammaddiyah Cingkariang Orphanage and to understand the efforts made by the orphanage in supporting education. The research findings reveal that the orphanage plays a crucial role in providing formal education services, offering elementary, middle school, and high school education, allowing children the freedom to choose their preferred schools. Additionally, the orphanage provides informal education, specifically religious education through Quran memorization. In summary, the Muhammaddiyah Cingkariang Orphanage fulfills the educational needs of orphaned children, aligning with their rights to both formal and informal education, similar to what they might receive in their biological families